Forest-based biomass energy concepts and applications - Spellman, Frank R. (CRC Press, 2012)
"This reference covers renewable energy derived from natural processes that are replenished continuously in various forms, such as biofues, bio-products, and bio-power. The book provides an overview of renewable and sustainable energy and an explanation of the science and mathematics of biomass. It examines numerous types of biomass feedstocks, and includes coverage on converting biomass waste into useable energy. Tree stocks covered include Poplar, Willow, American Sycamore, Sweetgum, and Loblolly. It also offers information on the benefits of Agroforestry, the approach of combining crops with livestock. "--Provided by publisher.
Keywords: Forest biomass.; Biomass energy.; elektronické knihy; electronic books